Saving the food value chain amid Covid lockdown - Sekhara Rao N., Chandra; Kumar, Anjani (Kasturi & Sons, 2020)
Disruptions in the food value chain are becoming visible now. The government needs to recognise that ensuring adequate food and nutrition for the population is as essential as providing health services.